INTERNALISASI MODERASI DALAM KARAKTERISTIK HUKUM ISLAM: Studi Kasus Aplikasi Moderasi Ummat Islam di Kab. Ketapang - Miskari Bin Ahmad (Fakultas Syariah (Syari'ah Faculty ), 2022)
This study will examine the life of the Ketapang Muslim community who live in religious and multi-ethnic pluralism but still adhere to the teachings of their respective religions and maintain religious tolerance, especially for Muslims as the majority religion, but still internalize the values of moderation. in the messages of Islamic sharia teachings. This study will provide understanding and original concepts sourced from the Koran and Hadith, then translated by scholars so that the characteristics of moderate Islamic law are structured and become mercy to the universe. The purpose of this study is that every modern Muslim can understand and implement the values of moderation in his daily life, can interact well with non-Muslims around him, no need to hesitate with the application of Islamic laws that he believes in. So that what he does is not considered contrary to Islamic law properly and comprehensively in his daily life. This study uses library methods and field observations on the behavior and application of moderation values in accordance with the characteristics of Islamic law sourced from the Qur'an, As-Sunnah and classical and modern books from classical and contemporary scholars who are qualified and expert in their field. The literature and findings in the field will be carefully studied and analyzed by researchers to produce appropriate and tested conclusions. The results of this study found that the life of the Ketapang Muslim community highly upholds religious moderation, especially the Muslims, who internalize the values of moderation based on the characteristics of Islamic law.